Noise Risk Assessment in the Workplace: The Case of a Waste Selection Plant. (May 2015) - Kaliakatsos, Dimitrios; Mirabelli, Giovanni; Pizzuti, Teresa
This paper deals with issues related with the exposure of workers to noise pollution. The aim of the research work is to define and analyse the effects of noise pollution within the working environment. The paper presents the results of the analysis carried out for a company operating various activities of screening, sorting and recycling waste produced in the urban context. Focusing on the company context, the authors studied the operating conditions in which workers performed their activities, they established the methodologies and tools in order to carry out noise measurements and they evaluated the presence of hazardous conditions. Finally, the authors suggest different operational and structural solutions for controlling risks for health of workers and the reduction of noise emissions in the environment.